Pengaruh Budaya Nasional dan Partisipasi Anggaran terhadap Kesenjangan Anggaran pada Organisasi - Ririn Handayani; Eka Afnan Troena; Umar Nimran; Mintarti Rahayu (Jurnal Aplikasi Manajemen, 2012)
This type of research is categorized as explanatory research. The target population of this research is the entire structural officers in 11 regencies/cities of Riau Province. Accessible population is entire structural officers in 4 technical boards. Applying stratified random sampling, total sampling is 140, out of 135 returned questionnaires, 124 is good for the purpose of analysis. Structrual Equation Modelling (SEM) with AMOS software 6 version is used to examine the relationship among variables. Based on data analysis where the finding is also supported by sistematic variance of financial statement of each respective regencies/cities. Several results also generate; first , national culture consisting of power distance, uncertainty avoidance, masculine vs feminine, individualism vs collectivism, short and long term orientation influences the budgetary slack in 11 regencies/cities of Riau Province. Second, the influence of national culture will be stronger if budget particiaptory exists. Several recommendations from this research are to utilize national culture by reducing power distance, uncertainty avoidance, more feminine and close to group as well long-term orientation that is expected to decrease the budgetary slack.Keywords: national culture, budget participatory, and budgetary slack